Kunst, die glücklich macht : Bilder von Fracesco Clemente, Jiri Georg Dokoupil, Jan Knap, Nicola de Maria, Gianmarco Montesano, Luigi Ontani, Salvo. (Stuttgart : Galerie Kaess-Weiss, 1993)
Clemente, Francesco ; Dokoupil, Jiri Georg ; Knap, Jan ; de Maria, Nicola ; Montesano, Gianmarco ; Ontani, Luigi ; Salvo
Kunst, die glücklich macht : Bilder von Fracesco Clemente, Jiri Georg Dokoupil, Jan Knap, Nicola de Maria, Gianmarco Montesano, Luigi Ontani, Salvo, Galerie Kaess-Weiss, Stuttgart, 18. September bis 30. Oktober 1993
German
kunstcatalogus